Utilizing Social Media Marketing: For Orang Ulu’s Handicraft Products Promotion - Qistina Donna, Lee Abdullah; Easther, Indang; Salmiah, Abdul Hamid; Aliffazraie, Jali; Marzie, Hatef Jalil; Mazdan, Ali Amaran (UNIMAS Publisher, 2025)
This paper deliberates on references of digital marketing strategies by utilizing social media marketing to promote Orang Ulu’s Handicraft products. The findings of this paper can significantly enhance the visibility and market reach of Orang Ulu’s handicraft products. This research involved 200 respondents who answered the research questionnaires. The data collected from the fieldwork were analyzed using SPSS version 26. The measures used in this article are methodically descriptive frequency analysis. The results of the descriptive means of all the analyzed items highlight and summarize the significance of social media platforms in marketing Orang Ulu’s handicraft products.